Regional Analgesia in Video-Assisted Thoracic Surgery: A Bayesian Network Meta-Analysis - Lin, Jingfang; Liao, Yanling; Gong, Cansheng; Yu, Lizhu; Gao, Fei; Yu, Jing; Chen, Jianghu; Chen, Xiaohui; Zheng, Ting; Zheng, Xiaochun (Frontiers in Medicine, 2022)
Background: A variety of regional analgesia methods are used during video-assisted thoracic surgery (VATS). Our network meta-analysis (NMA) sought to evaluate the advantages of various methods of localized postoperative pain management in VATS patients. Methods: PubMed, the Cochrane Library, and EMBASE were searched from their date of inception to May 2021 for randomized controlled trials (RCTs) comparing two or more types of locoregional analgesia in adults using any standardized clinical criteria. This was done using Bayesian NMA. Results: A total of 3,563 studies were initially identified, and 16 RCTs with a total of 1,144 participants were ultimately included. These studies, which spanned the years 2014 to 2021 and included data from eight different countries, presented new information. There were a variety of regional analgesia techniques used, and in terms of analgesic effect, thoracic epidural anesthesia (TEA) [SMD (standard mean difference)=1.12, CrI (Credible interval): (-0.08－-2.33)], thoracic paravertebral block (TPVB) (SMD=0.67, CrI: (-0.25－1.60) and erector spinae plane block (ESPB) (SMD=0.34，CrI: (-0.5－1.17) were better than other regional analgesia methods. Conclusion: Overall, these findings show that TEA, TPVB and ESPB may be effective forms of regional analgesia in VATS. This research could be a valuable resource for future efforts regarding the use of thoracic regional analgesia and enhanced recovery after surgery.